Bacteriophage T4 Inhibits Colicin E2-Induced Degradation of Escherichia coli Deoxyribonucleic Acid I. Protein Synthesis-Dependent Inhibition - Swift, Robert L. (1971)
The deoxyribonucleic acid (DNA) of Escherichia coli B is converted by colicin E2 to products soluble in cold trichloroacetic acid; we show that this DNA degradation (hereafter termed solubilization) is subject to inhibition by infection with bacteriophage T4. At least two modes of inhibition may be differentiated on the basis of their sensitivity to chloramphenicol. The following observations on the inhibition of E2 by phage T4 in the absence of chloramphenicol are described: (i) Simultaneous addition to E. coli B of E2 and a phage mutated in genes 42, 46, and 47 results in a virtually complete block of the DNA solubilization normally induced by E2; the mutation in gene 42 prevents phage DNA synthesis, and the mutations in genes 46 and 47 block a late stage of phage-induced solubilization of host DNA. (ii) This triple mutant inhibits equally well when added at any time during the E2-induced solubilization. (iii) Simultaneous addition to E. coli B of E2 and a phage mutated only in gene 42 results in extensive DNA solubilization, but the amount of residual acid-insoluble DNA (20 to 25%) is more characteristic of phage infection than of E2 addition (5% or less). (iv) denA mutants of phage T4 are blocked in an early stage (endonuclease II) of degradation of host DNA; when E2 and a phage mutated in both genes 42 and denA are added to E. coli B, extensive solubilization of DNA occurs with a pattern identical to that observed upon simultaneous addition of E2 and the gene 42 mutant. (v) However, delaying E2 addition for 10 min after infection by this double mutant allows the phage to develop considerable inhibition of E2. (vi) Adsorption of E2 to E. coli B is not impaired by infection with phage mutated in genes 42, 46, and 47. In the presence of chloramphenicol, the inhibition of E2 by the triple-mutant (genes 42, 46, and 47) still occurs, but to a lesser extent.